Violence, resistance and citizenship in rural locations of colombia. comparisons (2013)
This article discusses the analysis of resistance against the actors, shocks and effects of war in peripheral areas of the central regions, that is, in traditional peasant towns framed by more than a century in the institutional and economic networks that structure Colombian nation, but situated in the most disjointed and excluded from the regions surrounding major metropolitan cities. The text examines the apparent differences in the interaction between armed groups and residents in outlying subregions of ancient settlement and the strong bonds of social identity, where armed groups, guerrillas and paramilitaries were in the early stages of a significant expansion.